1991
DOI: 10.1007/bf00328401
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soil drying on root development, water relations and leaf growth of Ceratonia siliqua L.

Abstract: Seedlings of Ceratonia siliqua L., an evergreen sclerophyll species native to the Mediterranean region, were grown in 30-cm deep tubes of John Innes II potting compost in a growth cabinet maintained at 15° C during a 12-h day where PAR was 400 μmol m s. After a period of acclimatisation to the conditions in the cabinet during which plants were watered every day, water was withheld from the soil in some tubes for 24 days. These conditions may be regarded as a simulation of the natural situation. Estimates of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…Considering fruit production per unit of available water it is expected that non-irrigated trees would present higher rates of water use efficiency (Correia and MartinsLouqao, 1993b). Although soil drying will eventually reduce root growth (Rhizopoulou and Davies, 1991), it is also established that N accumulation is able to function not only as a N source but also as an osmoticum (Leidi and Lips, 1990). This is in agreement with recent work which shows that osmotic potential can control carob drought stress tolerance (Nunes et al, 1989) and could explain the low values of midday LWP in non-irrigated trees during the summer drought period (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Considering fruit production per unit of available water it is expected that non-irrigated trees would present higher rates of water use efficiency (Correia and MartinsLouqao, 1993b). Although soil drying will eventually reduce root growth (Rhizopoulou and Davies, 1991), it is also established that N accumulation is able to function not only as a N source but also as an osmoticum (Leidi and Lips, 1990). This is in agreement with recent work which shows that osmotic potential can control carob drought stress tolerance (Nunes et al, 1989) and could explain the low values of midday LWP in non-irrigated trees during the summer drought period (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Similar conclusions were suggested by Nunes et al (1992) also for mature carob-trees. Rhizopoulou and Davies (1991) also found that, in young carob tree plants submitted to soil water deficit for 3 weeks, deep penetration of some roots was enough to supply substantial amounts of water to shoot growth. On the other hand, the direct response of predawn LWP values to irrigation in 1991 (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…For these species, stomatal conductance of the drought-stressed plants started to decline when the volumetric soil moisture reached approximately 50% of avail- smaller than in the other species, which would lead to a higher sensitivity of stomata to soil drought. A prolonged, comparative study of the biology of root development and water status in relation to drought stress between species of these two subgenera might contribute to a better understanding of these observed differences (Rhizopoulou & Davies, 1991). able capacity.…”
Section: Resultsmentioning
confidence: 99%
“…Eqn 2 Turgor is well maintained in plants subjected to water deficit (Rhizopoulou & Davies, 1991), to changes in temperature (Pritchard et al, 1990) or to nitrogen deprivation (Palmer et al, 1996). Changes in expansion rate are therefore essentially linked to cell-wall rheological properties, via the activities of enzymes such as xyloglucan endotransglycosylase (XET) (Pritchard et al, 1993), expansins (MacQueen-Mason & Cosgrove, 1995 ;Reinhardt et al, 1998) or peroxidases (Thompson et al, 1998), under the control of chemical signals such as ABA (Ben Haj Salah & Tardieu, 1997) and\or of hydraulic signals (Chazen & Neuman, 1994 ;Ben Haj Salah & Tardieu, 1997).…”
Section: F Tardieu Et Almentioning
confidence: 99%